Impact of production season on the chemical composition and health properties of goat milk and rennet cheese - Katarzyna Ząbek, Stanisław Milewski; Antoszkiewicz, Zofia; Alicja Sobczak, Zenon Tański (Emirates Journal of Food and Agriculture, 2018)
This study compared selected parameters of milk and rennet cheese produced from milk obtained from alpine goats during winter and summer feeding under climatic conditions of the Warmia and Mazury region. Milk from the winter season contained more protein, less vitamin A and over seven times less vitamin E than milk obtained in summer. In cheese from the winter season, the content of dry matter, fat, protein and vitamin A was lower when compared with cheese from the summer period. The content of total biogenic amines in cheese was almost twice as high in winter than in summer (1056.4 vs 567.6 mg/kg). Winter cheese contained more cadaverines and histamine than summer cheese. The content of tyramine and putrescine was comparable in cheese from both seasons and was higher than the level of histamine. Milk fat from milk obtained in winter contained more long-chained SFA and MUFA in comparison with the summer period. Fat from cheese produced in summer had a higher content of SFA, CLA and ALA, whereas cheese from the period of winter feeding contained more C16:0izo and C18:1. The content of hyper- and hypocholesterolemnic acids was comparable in milk and in cheese with a slightly smaller proportion of hyper-acids and a slightly higher proportion of hypocholesterolemnic acids during summer feeding of goats. In conclusion, it was found that the feeding season had a minor impact on the chemical composition of milk, although it significantly differentiated the chemical composition of rennet cheese produced from that milk and the health quality parameters of both products. Milk from winter feeding had a higher content of protein, whereas the chemical composition of cheese was more beneficial in winter as the content of dry matter, fat and protein was higher. The health properties of both products were more beneficial in summer, which was determined by the profile of fatty acids and the content of vitamin A.